En busca de los irlandeses y de los estudios irlandeses en Australia - Elizabeth Malcolm (Estudios Irlandeses, 2019)
The Irish-Australian story is different in important respects from the Irish story in other parts of the diaspora. Therefore, before embarking upon any discussion of the writing or teaching of Irish Studies, it is important for readers to appreciate some of the main characteristics of the Irish experience in Australia. Between 1800 and 2000, many more people left Ireland for the United States or Britain than for Australia. Unlike these older nations, Australia was a new settler society on the far side of the world. Its attractions were limited and travel there was expensive. Six British colonies had been established across the continent between the 1780s and the 1850s and, in 1901, these joined together in a federation to form the Commonwealth of Australia, a British dominion, which in that year had a white population of only 3.8 million. It has been estimated that Irish immigrants and their Australian-born offspring constituted around one-quarter of this population. In other words, the Irish formed a larger proportion of the general population in Australia than in probably any other diaspora country. They were a substantial ethnic minority, second only in numbers to those of English birth and descent (Price).